Boron nitride nanotubes and nanoplatelets as reinforcing agents of polymeric matrices for bone tissue engineering. Issue 2 (3rd November 2015) - Farshid, Behzad; Lalwani, Gaurav; Shir Mohammadi, Meisam; Simonsen, John; Sitharaman, Balaji
Abstract: This study investigates the mechanical properties and in vitro cytotoxicity of one‐ and two‐dimensional boron nitride nanomaterials‐reinforced biodegradable polymeric nanocomposites. Poly(propylene fumarate) (PPF) nanocomposites were fabricated using crosslinking agent N ‐vinyl pyrrolidone and inorganic nanomaterials: boron nitride nanotubes (BNNTs) and boron nitride nanoplatelets (BNNPs) dispersed at 0.2 wt % in the polymeric matrix. The incorporation of BNNPs and BNNTs resulted in a ∼38 and ∼15% increase in compressive (Young's) modulus, and ∼31 and ∼6% increase in compressive yield strength compared to PPF control, respectively. The nanocomposites showed a time‐dependent increased protein adsorption for collagen I protein. The cytotoxicity evaluation of aqueous BNNT and BNNP dispersions (at 1–100 μg/mL concentrations) using murine MC3T3 preosteoblast cells showed ∼73–99% viability. The cytotoxicity evaluation of media extracts of nanocomposites before crosslinking, after crosslinking, and upon degradation (using 1×–100× dilutions) showed dose‐dependent cytotoxicity responses. Crosslinked nanocomposites showed excellent (∼79–100%) cell viability, cellular attachment (∼57–67%), and spreading similar to cells grown on the surface of tissue culture polystyrene control. The media extracts of degradation products showed a dose‐dependent cytotoxicity. The favorable cytocompatibility results in combination with improved mechanical properties of BNNT and BNNP nanocomposites opens new avenues for further in vitro and in vivo safety and efficacy studies towards bone tissue engineering applications. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 406–419, 2017.